The New digital era : digitalisation, emerging risks and opportunities - Grima, Simon; Özen, Ercan; Boz, Hakan (Contemporary studies in economic and financial analysis ;, 2022)
The COVID-19 pandemic has led to further acceleration of digitalisation in all areas. This caused significant changes in economic and social life. Through digitalisation, the need for people in business life has decreased and has forced the traditional employment structure to change. During the pandemic period, some segments enjoyed the advantages of owning digital technologies, while others remained strangers to the new world because they were deprived of digital technologies, revealing the inequality of opportunity on an individual or social basis. Although this rapid change produced positive results, it also brought about risks. To help mitigate such emerging risks, The New Digital Era's two volumes vitally generate new information in order to determine the advantages and risks in which areas this digitalisation, which has increased with the COVID-19 pandemic. The chapter authors highlight the new social and economic policies that are needed to balance the effects on social and economic life and prevent possible conflicts between individuals and societies Contemporary Studies in Economic and Financial Analysis publishes a series of current and relevant themed volumes within the fields of economics and finance. Both disciplinary and interdisciplinary studies are welcome.